Neurobeachin regulates receptor downscaling at GABAergic inhibitory synapses in a protein kinase A-dependent manner - Felix P. Lützenkirchen; Yipeng Zhu; Hans M. Maric; Dominik S. Boeck; Kira V. Gromova; Matthias Kneussel (Communications Biology)
Abstract GABAergic synapses critically modulate neuronal excitability, and plastic changes in inhibitory synaptic strength require reversible interactions between GABAA receptors (GABAARs) and their postsynaptic anchor gephyrin. Inhibitory long-term potentiation (LTP) depends on the postsynaptic recruitment of gephyrin and GABAARs, whereas the neurotransmitter GABA can induce synaptic removal of GABAARs. However, the mechanisms and players underlying plastic adaptation of synaptic strength are incompletely understood. Here we show that neurobeachin (Nbea), a receptor trafficking protein, is a component of inhibitory synapses, interacts with gephyrin and regulates the downscaling of inhibitory synaptic transmission. We found that the recruitment of Nbea to GABAergic synapses is activity-dependent and that Nbea regulates GABAAR internalization in a protein kinase A (PKA)-dependent manner. In heterozygous neurons lacking one Nbea allele, re-expression of Nbea but not expression of a PKA binding-deficient Nbea mutant rescued the internalization of GABAARs. Our data suggest a mechanism by which Nbea mediates PKA anchoring at inhibitory postsynaptic sites to downregulate GABAergic transmission. They emphasize the importance of kinase positioning in the regulation of synaptic strength.